Sustainable forest management and carbon in tropical Latin America: the case for REDD+ - Nasi, Robert; Putz, F.E.; Pacheco, P.; Wunder, Sven; Anta, S. (MDPI, 2011)
In this review paper, we assess the economical, governance, and technical conditions that shape forest management in tropical Latin America with particular regard to efforts to reduce forest-based carbon emissions. We provide a framework for discussions about ways to improve forest management that achieve environmental objectives while promoting local and national development and contributing to local livelihoods. We argue that many management practices that lead towards sustainability are only likely to be adopted where there is good governance backed by financial incentives for effective enforcement of management regulations. We propose some policy interventions designed to lower net greenhouse gas emissions by decreasing rates of forest degradation and increasing carbon stock recovery in logged-over or otherwise degraded forests. Implementation of REDD+ could provide critical compensation to forest users for improved management practices in the absence of, or in combination with other economic incentives.